2018
DOI: 10.2174/1872210511666170920144342
|View full text |Cite
|
Sign up to set email alerts
|

Technological Prospection on Membranes Containing Silver Nanoparticles for Water Disinfection

Abstract: The countries with the most academic output and priority patents are the United States and China, but no institution stands out from the others in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, it is reported that the free radicals can be generated when AgNPs are in contact with bacteria [22]. However, the mechanism underlying the antimicrobial effects of AgNPs is not fully understood and remains debatable [23,24]. In addition, the effect of AgNPs on the antifouling properties of fabricated membranes has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is reported that the free radicals can be generated when AgNPs are in contact with bacteria [22]. However, the mechanism underlying the antimicrobial effects of AgNPs is not fully understood and remains debatable [23,24]. In addition, the effect of AgNPs on the antifouling properties of fabricated membranes has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%